1982
DOI: 10.1136/thx.37.3.169
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary epithelial permeability is immediately increased after embolisation with oleic acid but not with neutral fat.

Abstract: Pulmonary fat embolism occurs frequently after trauma but its functional significance is often unclear. To obtain direct evidence of lung damage caused by fat embolism we have measured changes in permeability of the alveolar-capillary interface. A permeability index was derived from the half time clearance from lung to blood (T-LB) of 99mTc DTPA introduced into the lung in a 1 ml bolus. Three groups ofrabbits were studied. Baseline Tw LB. did not differ significantly between groups. After intravenous injection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

1985
1985
2008
2008

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 7 publications
2
17
0
Order By: Relevance
“…After this rapid rise the appearance of FITC-dextran in the blood was similar in OAPE and control. This observation is consistent with the findings of Jones et al (20) and suggests a rapid control ofthe leak after the oleic acid damage. Recent studies by Dvorak et al (21) have shown that extravascular coagulation can be initiated by large microvascular leaks, and the presence of fibrin on the alveolar surface (Fig.…”
Section: Fitc Tracer Studiessupporting
confidence: 82%
See 1 more Smart Citation
“…After this rapid rise the appearance of FITC-dextran in the blood was similar in OAPE and control. This observation is consistent with the findings of Jones et al (20) and suggests a rapid control ofthe leak after the oleic acid damage. Recent studies by Dvorak et al (21) have shown that extravascular coagulation can be initiated by large microvascular leaks, and the presence of fibrin on the alveolar surface (Fig.…”
Section: Fitc Tracer Studiessupporting
confidence: 82%
“…6 d) suggest that this occurred in OAPE. The observations from these studies and others (20,21) therefore suggest that the fibrin deposition in alveoli that occurs as part of hyaline membrane formation may be a manifestation ofextravascular coagulation that occurs in an attempt to control large microvascular leaks.…”
Section: Fitc Tracer Studiesmentioning
confidence: 94%
“…However, there are difficulties in obtaining satisfactory samples, as shown in one study where only 67 out of 96 samples were adequate for analysis due to low yield of macrophages [24]. Also, the stain used in these investigations is a stain for neutral fat (oil red O) which does not produce lung injury [25]. Despite these reservations, the use of a threshold value (such as 30%) of macrophages staining positive might be useful in trauma patients.…”
Section: Q 2001 Blackwell Science Ltdmentioning
confidence: 99%
“…A flaw in this theory is that neutral fats are the major constituents of bone marrow and they do not display this effect [25]. However, it is highly likely that in vivo there is hydrolysis of neutral fats to FFAs and this may help explain the symptom-free interval before the onset of signs and symptoms during which hydrolysis occurs.…”
Section: Lipase Theorymentioning
confidence: 99%
“…The presence of microemboli was, however, confirmed at least for 12 h by electron microscopy. Triolein can be hydrolyzed to free fatty acid or oleic acid [19] , which was reported to have more potent effects for vascular permeability and toxicity [7,26] . Diffuse leakage of fluorescein at 4 h would represent the diffuse alteration of the BRB caused by the hydrolyzed fatty acid.…”
Section: Discussionmentioning
confidence: 99%